Effectiveness of Auricular Acupuncture on Interleukin-6 Levels and the Duration of Birth Delivery in Primigravida Mothers during Active Phase of Labor - Setiawandari, Setiawandari; Andarwulan, Setiana; Hubaedah, Annah (Journal of Maternal and Child Health, 2023)
Background: Auricular acupuncture (AKAR) is a diagnostic and treatment system based on normalizing bodily dysfunctions through stimulation of specific points on the ear. Ear stimulation involves neurological reflexes, neurotransmitters, cytokines, the immune system, and inflammation. Subjects and Method: This study is a true experimental design with a pretest-posttest control group. The study population was all 43 primigravida mothers who were expected to give birth between May and July 2023. The research sample was part of the first stage of labor during the primigravida active phase. The selection of research subjects was carried out by consecutive sampling. Subjects who met the inclusion criteria were divided into two groups, namely the AKAR intervention group and the deep breathing relaxation control group. The dependent variable was auricular acupuncture, and the independent variable was a duration of labor and interleukin-6. The instrument uses laboratory tests that are carried out, the research site only has a simple laboratory room and does not have a deep freezer - 800C, so the biomarker test is carried out in the laboratory. Assessment of the length of labor using a partograph. Data analysis used the Mann-Whitney test,  the Wilcoxon Signed Rank test and the Independent  Sample test Results: The results of post-treatment serum IL-6 levels in the AKAR group were higher (Mean= 187.24; SD= 41.65) pg/mL before the pre-treatment (Mean= 157.67; SD= 51.85) pg/mL, and this difference was significant (p <0.001). Post-treatment serum IL-6 levels in the RND group were higher (Mean= 181.30; SD= 56.86) pg/mL before the pre-treatment (155.65; SD= 50.07) pg/mL. The results of the pre-treatment serum IL-6 levels in the AKAR group were slightly higher (Mean= 157.67; SD= 51.85) pg/mL compared to the RND group (Mean= 155.65; SD= 50.07) pg/mL. Post-treatment, the IL-6 serum level in the AKAR group were higher (Mean= 187.24; SD= 41.65) pg/mL compared the RND group (Mean= 181.30; SD=56.86) pg/mL. The AKAR group had 12 (57%) active phase I stages of labor that lasted less than 360 minutes and 9 (33%) more than 360 minutes. In the RND group, 9 (45%) delivered less than 360 minutes, and 11 (55%) more than 360 minutes. The mean length of labor for the AKAR group was shorther (Mean= 365.40; SD= 65.60) minutes than the RND group (Mean= 407.55; SD = 77.27). Conclusion: There was a difference between IL-6 levels before and after treatment, so it was concluded that AKAR and RND affected serum IL-6 levels in the first stage of labor in the active primigravida phase. There was no significant difference in the length of labor in the active phase of the first stage of labor in primigravidas between AKAR and RND. Keywords: acupuncture, auricular, interleukin-6, length of labor. Correspondence: Setiana Andarwulan. Program Study Midwife Professional Education, Faculty of Science and Health, PGRI Adi Buana University, Surabaya Jl Dukuh Menanggal XII No. 4, East Java, Indonesia. Email: setianaandarwulan@unipasby.ac.id. Mobile: 085806227033.